Sestojne padavine v mešanih sestojih smreke in bukve na Pohorju - Vilhar, Urša (Gozdarski vestnik, 2016)
Net precipitation in forests consists of water (throughfall), reaching the ground through canopy gaps or dripping from the foliage or branches and stemflow. In this study, the effect of tree species conversion in spruce monocultures into mixed deciduous-coniferous forests in Pohorje on net precipitation was investigated. Such changes might affect hydrological processes on the general catchment scale, since higher share of deciduous trees in mixed forests contributes to higher throughfall and stemflow and lower canopy interception. Four Norway spruce forests and four mixed spruce-beech forests in the Upper Oplotnica River catchment on Pohorje with varying share of spruce and beech in the growing stock were investigated. Net precipitation was estimated for each forest from measured or estimated throughfall and stemflow for the period from 2008 to 2014. Annual throughfall in selected forests ranged from 76 % to 82 % of the bulk precipitation. Annual stemflow was present only in two forests, ranging from 3 % to 12 % of the bulk precipitation, respectively. Annual net precipitation averaged to 92 % of the bulk precipitation, ranging from 99 % for the dormancy to 89 % for the growing season. Therefore, annual net precipitation was decreasing with increasing share of spruce in the growing stock, indicating higher canopy interception in mixed forests with prevailing spruce. In addition, the average net precipitation during the growing season was 10 % lower than during the dormancy, indicating higher interception during the growing season. Net precipitation is important indicator of hydrologic functions of forests (e.g. forest ecosystem services, related to water provisioning and regulating), since it is indicating the canopy interception capacity. The results of this study could contribute to the implementation of hydrology-oriented sylvicultural measures on a catchment scale, aiming at improved hydrological functions of forests.
Keywords: prepuščene padavine; odtok po deblu; mešanost drevesnih vrst; smrekove monokulture; premena